2007
DOI: 10.1002/mds.21326
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy case of opsoclonus–myoclonus–ataxia and cerebellar cognitive affective syndrome associated with small cell carcinoma of the lung

Abstract: We report an autopsy case of paraneoplastic opsoclonus-myoclonus-ataxia syndrome associated with small cell carcinoma of the lung. Chemotherapy and lung lobectomy resulted in complete tumor remission and disappearance of myoclonus. However, emotional and behavioral disturbances relapsed and remitted associated with exacerbation of truncal ataxia and ocular flutter, which responded favorably to prednisolone. At autopsy, after 2 years and 11 months of illness, there was no recurrence of cancer. Neuropathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…Lesions of the pons involving damage to the omnipause cells, which normally inhibit the burst neurons responsible for generating the saccadic impulse,7 or cerebellar lesions interrupting normal vermian inhibition of the fastigial nucleus, which regulates vestibular nuclear tone to burst neurons,8–11 have been suspected. Impairment of the dentatothalamocortical pathway has also been suggested,12 and supported by studies that have iden-tifed histological and biochemical alterations in the dentate nuclei 13,14. Concurrent pontine and cerebellar involvement has also been proposed 15…”
Section: Discussionmentioning
confidence: 90%
“…Lesions of the pons involving damage to the omnipause cells, which normally inhibit the burst neurons responsible for generating the saccadic impulse,7 or cerebellar lesions interrupting normal vermian inhibition of the fastigial nucleus, which regulates vestibular nuclear tone to burst neurons,8–11 have been suspected. Impairment of the dentatothalamocortical pathway has also been suggested,12 and supported by studies that have iden-tifed histological and biochemical alterations in the dentate nuclei 13,14. Concurrent pontine and cerebellar involvement has also been proposed 15…”
Section: Discussionmentioning
confidence: 90%
“…In this study, a neuroimaging abnormality in the cerebellum and midbrain was demonstrated in Patients 1 and 3, respectively. Few studies have been conducted concerning the autopsy brain finding of OMS, but some case reports have disclosed a reduced number of Purkinje cells in the cerebellum 7. Moreover, surface‐binding antibodies against cerebellar neurons were demonstrated in children with OMS 8.…”
Section: Discussionmentioning
confidence: 99%
“…After exclusion of structural and infective causes, OMS can be either idiopathic or paraneoplastic 27. Median age in one comparative study was 66 years in the paraneoplastic group and 40 in the idiopathic group, with none in the paraneoplastic group being younger than 50 years 28. Encephalopathy was almost exclusively seen in the paraneoplastic group and this could be severe and fatal in some.…”
Section: Opsoclonus Myoclonus Syndromementioning
confidence: 99%
“…Encephalopathy was almost exclusively seen in the paraneoplastic group and this could be severe and fatal in some. In most cases CSF and MRI brain scans are entirely normal or show nonspecific changes in the brainstem and cerebellum in a minority 28…”
Section: Opsoclonus Myoclonus Syndromementioning
confidence: 99%
See 1 more Smart Citation